FrameWeb-LD : uma abordagem baseada em ontologias para a Integração de Sistemas de Informação Web e a Web Semântica - Celino, Danillo Ricardo (2017)
With the enormous amount of data available on the Web, Linked Data technologies have been proposed to try and achieve the vision of the Semantic Web, allowing the efficient access, discovery and combination of the available data. Such data should be published in a structured way and bound to known vocabularies, so they can be understood by software agents. Moreover, the abstract conceptual models behind this data, i.e., their ontologies, can also have a great influence in the adoption of a Linked Data set and its vocabularies. In 2007, a Web Engineering method for the design and development of Web applications based on frameworks, named FrameWeb, was proposed, along with an extension of the method, called S-FrameWeb, that proposed the subsequent integration of the applica tion’s data with the Semantic Web. Given the advances of the literature in this area of research, such as well-founded ontologies and the evolution of Linked Data technologies, we propose an evolution of S-FrameWeb called FrameWeb-LD, an approach for the integration of Web-based Information Systems with the Semantic Web. Our proposal uses well-founded languages and methods for the construction of ontologies and aids developers in publishing the application’s data and services in the Web of Data, by offering a system atic process that brings to architectural design models how the data from the system is integrated with Semantic Web vocabularies and a tool that generates automatically most of the source code related to Linked Data publishing